Level of job satisfaction of campus development and maintenance office workers in the university of the Philippines in the Visayas, Miag-ao, Iloilo - Garcia, GG Lyn; Miralles, Queny Roselle; Olaguer, Rhea Melissa; Jermina, Jane; Genodepa, Stephen
This study aims to determine the general level of job satisfaction of the Campus Development and Maintenance Office (CDMO) workers and the relationship between the level of their job satisfaction and the facet of job satisfaction such as work, pay, supervisor, co-workers, and promotion. This is a survey research using the Job Descriptive Index questionnaire in data collection. Five components of facet satisfaction were utilized: the nature of work, pay, promotion, supervisor and interpersonal relaitonship. The study reveals that satisfaction in the different aspects or facet does affect the overall satisfaction level. Higher facet satisfaction would yield a higher level of global satisfaction.